2007
DOI: 10.1108/01604950710721548
|View full text |Cite
|
Sign up to set email alerts
|

Electronic books and the humanities: a survey at the University of Denver

Abstract: Purpose -To identify levels of awareness and patterns of usage of electronic books by scholars in the humanities. Design/methodology/approach -A survey of the University of Denver community assessed knowledge about and usage of electronic books. The results for humanists are presented here. Findings -Scholars in the humanities have a higher level of awareness of e-books than their colleagues across campus but use e-books at the same rate. Their patterns of use are different, with humanists using less of the e-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 8 publications
2
44
0
Order By: Relevance
“…He concludes, "clearly most users do not immerse themselves in electronic texts." 20 For Gregory, the "results suggest that students use e-books in a manner similar to how they use e-journals." 21 The study by Berg, Hoffman, and Dawson describes readers' treatment of e-books as "searching for discrete pieces of information."…”
Section: How E-books Are Used and By Whommentioning
confidence: 99%
“…He concludes, "clearly most users do not immerse themselves in electronic texts." 20 For Gregory, the "results suggest that students use e-books in a manner similar to how they use e-journals." 21 The study by Berg, Hoffman, and Dawson describes readers' treatment of e-books as "searching for discrete pieces of information."…”
Section: How E-books Are Used and By Whommentioning
confidence: 99%
“…51 Levine-Clark explored e-book use in the humanities. 52 While he found that "humanists (and social scientists) have a higher degree of awareness about electronic books than the rest of the university community," given their heavy reliance on the library catalog as part of their research process, this awareness did not translate to greater e-book use. 53 Finally, Nicholas, Rowlands, and Jamali examined e-book use among business and management students as part of the JISC National e-Book Observatory study, finding that "business students are major and significant users of e-books and e-textbooks and that they view them more frequently, spend longer viewing them, [and] view more of them."…”
Section: Disciplinary Differencesmentioning
confidence: 99%
“…The addition of bibliographic records for each e-book has been demonstrated to significantly increase use. 7 Faculty and, particularly, graduate students rely heavily upon the library's catalogue to locate and access ebooks. 8 Some libraries have even observed a doubling in usage.…”
mentioning
confidence: 99%